2018
DOI: 10.3390/ma11010132
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Composition, Structure, and Physical and Chemical Properties of Aluminium-Oxide-Based Sorbents on Water Adsorption Ability

Abstract: Interaction between the water adsorption ability of aluminium-oxide-based sorbents and their chemical composition, acid-base properties of the surface, and textural characteristics has been analysed. Alumina desiccants were synthesized with the centrifugal–thermal activation of gibbsite followed by the hydration of the gibbsite under mild conditions. It was demonstrated that the multicyclic adsorption regeneration of samples under realistic conditions results in structural transformations and changes in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
2
14
0
1
Order By: Relevance
“…The most important differences regarding water release curves occur above 180 • C, since water bound to ammonium salts were found in great amount over 1500-3000 s (in Canepari et al (2013) [11] in the temperature range 180-250 • C). Obtained results were in compliance with the water adsorption ability published previously by Canepari et al [11] and Zotov et al [39]. Thermal decomposition points for most inorganic salts used int his work oscillates above 200 °C; while the extraction temperature used in this study was 180 °C (a direct limitation of the usage of polypropylene coated Teflon filters for testing, which decompose above 200 °C).…”
Section: Qualitative Determination Of Water Bound To Tsp and To Selecsupporting
confidence: 88%
See 1 more Smart Citation
“…The most important differences regarding water release curves occur above 180 • C, since water bound to ammonium salts were found in great amount over 1500-3000 s (in Canepari et al (2013) [11] in the temperature range 180-250 • C). Obtained results were in compliance with the water adsorption ability published previously by Canepari et al [11] and Zotov et al [39]. Thermal decomposition points for most inorganic salts used int his work oscillates above 200 °C; while the extraction temperature used in this study was 180 °C (a direct limitation of the usage of polypropylene coated Teflon filters for testing, which decompose above 200 °C).…”
Section: Qualitative Determination Of Water Bound To Tsp and To Selecsupporting
confidence: 88%
“…Correlation coefficients between TSP and precipitation values (r = −0.40) correspond well with correlations between TSP-bound water and precipitation (r = −0.40). Both the TSP mass and TSP-bound water mass were negatively correlated with air relative humidity RH%, which is probably due to the effect of pollutants scavenged by fog or cloud droplets and their Obtained results were in compliance with the water adsorption ability published previously by Canepari et al [11] and Zotov et al [39]. Thermal decomposition points for most inorganic salts used int his work oscillates above 200 • C; while the extraction temperature used in this study was 180 • C (a direct limitation of the usage of polypropylene coated Teflon filters for testing, which decompose above 200 • C).…”
Section: Relationship Between 24-h Measurements Of Tsp Tsp-bound Watsupporting
confidence: 83%
“…The study of the acid-base characteristics, modified with K and Na ions at the stage of obtaining the plastic paste of adsorbents by removing the curves of influence of the aqueous suspension pH of desiccant samples on the time, was carried out by the authors of [77]. The authors showed that a sharp alkalinization of the solution occurred in the first seconds of contact of the sample with distilled water.…”
Section: Modification Of Adsorbents Based On Aluminium Oxide With the Cations Of Alkaline Metalsmentioning
confidence: 99%
“…It can be expected that the use of a more efficient desiccant as a protective layer will allow not only protecting the primary layer against condensed moisture, but also enhancing the overall performance of the adsorber. It is known that the application of the energy saving method for obtaining a sorbent by means of thermal activation of gibbsite in reactors with a rotating heating surface without the use of traditional "pneumatic transport" leads to its cost saving, and the introduction of various modifying additions in the composition of the adsorbents, obtained by this technology, allows increasing the sorption capacity of aluminium oxides [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%